NPK 15-10-12 dengan Pengisi Abu Terbang: Pengembangan Pupuk dan Pengujian pada Tomat - Pebrianto Harnawan; Tumio Marisi Dame; Suryandi Perdana (Institut Pertanian Bogor, 2023)
PT Pupuk Sriwidjaja Palembang (PSP) produces 1,222 tons fly ash per month from the operation of a coal boiler with a capacity of 1x23 MW. Fly ash has potential physical properties and mineral content. The Government Regulation No.22 of 2021, which classifies fly ash as a non-B3 waste, open up opportunities to utilize fly ash in a fertilizer product. In this project, the development of NPK 15-10-12 fertilizer with fly ash as a filler and fertilizer testing on tomato plants has been conducted. The use of fly ash as a filler in the granulation process has no effect on crushing strength and nutrient content of N, P, and K. The effects of using fly ash in the granulation process are in the consumption of water and in the granule drying process. The greater the ratio of fly ash the more water needed in the granulation process and eventually causes an increase in the moisture content in the final product. From the results of fertilizer test on tomato plants on the parameters of plant height, plant diameter, and fruit weight, the use of NPK with fly ash-filler did not give a significant difference compared to the use of NPK without fly ash. The use of fly ash as a filler also does not give any influence on the content of heavy metals in the fruit of tomato. Increase in pH of soil are observed in fertilization to NPK 15-10-12 using fly ash fillers. Keywords: fly ash, granulation, NPK Fertilizer, tomatoes